The Role of PSAK 105 in Mudharabah Financing Practices: A Case Study of KSPPS BMT Tumang - Risydiyani, Wilda; Aini, Qurotul; Fitriyani, Yeny (Universitas Trunojoyo Madura, 2025)
The Statement of Financial Accounting Standards (PSAK) 105 serves as the main reference in recording mudharabah transactions in Islamic financial institutions, including Islamic cooperatives. This study aims to examine the implementation of PSAK 105 in mudharabah financing at KSPPS BMT Tumang by reviewing four main aspects: recognition, measurement, presentation, and disclosure. The research uses a qualitative approach through case studies, with data obtained through in-depth interviews, field observations, and documentation studies during the period from December 2024 to January 2025. The research results show that the aspects of recognition and presentation are in accordance with the provisions of PSAK 105, especially in cash-based transactions. However, in the aspects of measurement and disclosure, limitations are still found, particularly in handling non-cash transactions and the transparency of external reports. Factors such as limited understanding of human resources, the absence of written policies, and minimal technical oversight by the Sharia Supervisory Board also affect the implementation of the standards. This study recommends strengthening internal capacity, formulating technical policies based on PSAK 105, and developing a more informative external reporting system to enhance the accountability and transparency of sharia microfinance institutions.